1991
DOI: 10.1073/pnas.88.2.473
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopic demonstration of a conformational change in bacteriorhodopsin involved in proton pumping.

Abstract: Infrared spectral changes in bacteriorhodopsin (bR) were followed during the slow decay of the M intermediate in the temperature region 240-260 K. The decay of the M form is characterized by the disappearance of the ethylenic bands and the bands indicating the reprotonation of the Schiff base. The route of Schiff-base reprotonation completely changes between 240 K and 260 K. At 240 K reprotonation occurs from Asp-85, the group to which the proton was released during M formation, and there is no pumping. At 260… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 30 publications
(36 reference statements)
7
79
1
Order By: Relevance
“…gain the C conformation, it is proposed that the proton originally on the Schiff base, but now donated to Asp-85 (L -M 1 transition), is returned to the Schiff base (M 1 -bR56 8) and no pumping occurs (Ormos, 1991). The upshot of this, as far as our approach is concerned, is that by regulating the temperature, M1 can be "frozen"…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…gain the C conformation, it is proposed that the proton originally on the Schiff base, but now donated to Asp-85 (L -M 1 transition), is returned to the Schiff base (M 1 -bR56 8) and no pumping occurs (Ormos, 1991). The upshot of this, as far as our approach is concerned, is that by regulating the temperature, M1 can be "frozen"…”
Section: Discussionmentioning
confidence: 94%
“…Recently, a procedure was reported that describes the means whereby bR can be trapped in either the M 1 or the M2 state (Ormos, 1991). The conformational marker bands in the Amide I region of the lR, M -bR difference spectrum differ markedly between M1 and M2 (There is some N present with M2.…”
Section: What This Thesis Work Contributes To Answering the Principalmentioning
confidence: 99%
See 2 more Smart Citations
“…The decay of the M-intermediate in the photocycle and the regeneration of the ground state are strongly slowed below 80% rh (46). The decay of the multiple M-states can also be locked around 220-260 K (88). It is interesting to note that the T 2 values at 243 and 213 K of the transmembrane R-helices for the fully hydrated PM were longer than those at 293 and 273 K, and the T 2 values of loops increased between 243 and 213 K (Table 3, Figure 7).…”
Section: Dynamics Of Phospholipids In the Pmmentioning
confidence: 99%